(untitled) (Archives of Criminology, 2023)
The purpose of this study is to collect the relevant data and to formulate the theoretical background of corporate crime from a Central-Eastern European perspective. One of the main goals of the study is to explore and elucidate the complex interrelationships between corporate crime and the Hungarian market economy’s functioning. The different approaches for defining white-collar and corporate crime are summarised. An overview of the theoretical background of such crime is given. The general economic situation in Hungary is discussed, along with various available data, in order to examine the extent of corporate crime in Hungary. A detailed guideline for the empirical study of these crimes is also presented.